International Financial Statistics, December 2015. (International Financial Statistics; International Financial Statistics ;, 2015)
This December 2015 issue of International Financial Statistics is a standard source of statistics on all aspects of international and domestic finance. The monthly printed issue of IFS reports current monthly, quarterly, and annual data, while the yearbook reports 12 observations of annual data. Most annual data on the CD-ROM and Internet begin in 1948; quarterly and monthly data generally begin in 1957; most balance-of-payments data begin in 1970. A nominal effective exchange rate index represents the ratio of an index of a currency's period-average exchange rate to a weighted geometric average of exchange rates for the currencies of selected countries and the euro area. When a country joins the IMF, it is assigned a quota that fits into the structure of existing quotas. Quotas are considered in the light of the member's economic characteristics and considering quotas of similar countries.